151k views
3 votes
If


f(x) = ((3 + x))/(x - 3)
what is

f(a + 2)
?

a)

(3 + f(a + 2))/(f(a) - 1)
b)

((5 + a))/((a - 1))
c)

((3 + a))/((a - 3)) + 2


User Valeriy
by
6.0k points

1 Answer

3 votes

Answer:

Option B:
(5+a)/(a-1)

Explanation:

Given function is:


f(x) = (3+x)/(x-3)

In order to find f(a+2), we have to put a=2 in place of x in the function

So,


f(a+2) = (3 + (a+2))/((a+2)-3)\\ =(3+a+2)/(a+2-3)\\ = (5+a)/(a-1)

Hence, we can see that option b is correct ..

User Sean Kleinjung
by
5.7k points